2013
DOI: 10.1353/not.2013.0009
|View full text |Cite
|
Sign up to set email alerts
|

What Employers Want: Entry-Level Qualifications for Music Librarians

Abstract: This study investigates skills and aptitudes required and preferred by institutions for entry-level professional employment in music librarianship. All announcements from the Music Library Association’s Job Placement Service’s Job List 2008–2011 were examined, and entry-level professional positions were extracted. Each was then categorized by primary responsibilities, and required and preferred qualifications were coded. Data indicate that while some required skills are common among the field’s specialties, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Project management remains a skill set that is in strong demand, not only in project management as a profession and career [7], [8], but also in other professions such as banking [9], construction management [10], information technology [11], [12], librarianship [13], [14], operations research [15], supply chain management (SCM) [16], and technical communication [17]. One study found that approximately 37% of jobs being recruited for in one professional field require project management skills [15].…”
Section: Challenges Of Preparing Project Managersmentioning
confidence: 99%
“…Project management remains a skill set that is in strong demand, not only in project management as a profession and career [7], [8], but also in other professions such as banking [9], construction management [10], information technology [11], [12], librarianship [13], [14], operations research [15], supply chain management (SCM) [16], and technical communication [17]. One study found that approximately 37% of jobs being recruited for in one professional field require project management skills [15].…”
Section: Challenges Of Preparing Project Managersmentioning
confidence: 99%
“…Advertisements have also been used to examine entry-level positions in specific subfields or specializations. For example, Clark (2013) examined job postings for entry-level music librarians and Baker et al (2013) used both job advertisements and the outcome of job searches to draw conclusions about the desired qualifications of entry-level science and technology librarians in academic libraries. In each of these studies, job advertisements provided useful insight into the experiences of entry-level librarians searching for their first position.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The library and information science (LIS) profession is undergoing a time of transition. Positions for LIS graduates in "traditional" library-based settings are becoming increasingly rare (Demers et al 2014;Clark 2013;Szkolar 2012;Fialkoff 2009;Stronski 2004). At the same time authors are highlighting the myriad opportunities available to LIS graduates in the information economy (Fagerheim 1999;Hovendick 2009).…”
Section: Introductionmentioning
confidence: 99%